Two-component supramolecular hydrogel, bone adhesive and preparation method of two-component supramolecular hydrogel and bone adhesive

By using the combination of tannic acid and steal glycoside to prepare dual component super molecular hydrogel bone adhesives, the existing bone adhesives are inadequate in terms of biocompatibility, antibacterial ability, and adhesion strength, and realize More efficient and safer fracture fixed effects.

CN119350646APending Publication Date: 2025-01-24SHANDONG UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411489541.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing bone adhesives have shortcomings in biocompatibility, antibacterial ability, bond strength and ease of use, which limits their application in the treatment of comminuted fractures.

Method used

Using a two-component supramolecular hydrogel, through the combination of tannic acid and steviol glycosides, chemical cross-linking is achieved by utilizing the π-π interaction of the benzene ring and the hydrogen bond interaction of the hydroxyl group, and a supramolecular cross-linked network is prepared Structural bone adhesive.

Benefits of technology

The bone adhesive has a strong bone adhesion strength, good biocompatibility and natural antibacterial ability, and can repeatedly adhesive, significantly improved the bone adhesion effect, and meet the performance requirements of clinical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350646A_ABST
    Figure CN119350646A_ABST
Patent Text Reader

Abstract

The invention discloses a bi-component supramolecular hydrogel, a bone adhesive and a preparation method of the bone adhesive, and relates to the technical field of medical adhesives. The preparation method comprises the following steps: uniformly mixing a tannic acid aqueous solution and a stevioside aqueous solution, standing and cross-linking to obtain the two-component supramolecular hydrogel. In the two-component supramolecular hydrogel, the mass ratio of the tannic acid to the stevioside is 1.7: (1.01-2.41). The two-component supramolecular hydrogel has relatively high bone bonding strength and good biocompatibility, and has natural antibacterial ability and repeated bonding performance. The bone adhesive prepared from the bi-component supramolecular hydrogel can better meet the performance requirements of clinical bone adhesives, is a novel bone adhesive with great application potential, and is more suitable for clinical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical adhesives, in particular to a two-component supramolecular hydrogel, a bone adhesive and a preparation method thereof. Background Art

[0002] Traditional treatments for fractures mainly use screws and plates to fix the fracture fragments. For comminuted fractures, the difficulty of surgical fixation increases significantly, and the reduced accuracy of splicing may affect the effect of bone repair. In addition, implants such as screws and plates cannot be degraded in the human body and have varying degrees of foreign body reactions, requiring secondary surgery to remove, which increases the patient's pain and economic burden. Therefore, it is necessary to develop new fracture fixation methods to solve the above problems.

[0003] Bone adhesives can quickly splice and fix fracture fragments, and are particularly suitable for comminuted fractures with a large number of small and irregular bone fragments. In addition, bone adhesives do not need to be removed after healing, which reduces the pain of patients and the risk of surgical treatment. Based on the above advantages, bone adhesives have become a very promising alternative to traditional fracture treatment. Bone adhesives used in clinical practice need to meet the following properties: 1. Sufficient bonding strength; 2. Good biocompatibility; 3. Good antibacterial ability; 4. Easy to use and operate, and moderate curing time. In clinical practice, cyanoacrylate was first used for fracture fixation. It has high bonding strength and short curing time, but poor biocompatibility and can cause tissue inflammation. Polymethyl methacrylate has been used as a bone adhesive in knee and hip replacement surgery. However, it may induce severe thermal necrosis during use, and its adhesion strength and biocompatibility are poor. Although calcium phosphate bone cement, fibrin adhesive, mussel adhesive protein and other biological bone adhesives show good biocompatibility, their mechanical strength and bonding strength are poor. In addition, the above types of bone adhesives do not have strong antibacterial ability. It can be seen that the bone adhesives currently developed cannot meet all performance requirements and are greatly limited in their clinical application in bone bonding and fixation. Summary of the invention

[0004] The purpose of the present invention is to provide a two-component supramolecular hydrogel, a bone adhesive and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The two-component supramolecular hydrogel has strong bone adhesion strength, good biocompatibility, natural antibacterial ability and repeated adhesion performance.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] The present invention provides a method for preparing a two-component supramolecular hydrogel, comprising the steps of uniformly mixing a tannic acid aqueous solution and a stevioside aqueous solution, and then allowing the mixture to stand for cross-linking to obtain the two-component supramolecular hydrogel;

[0007] In the two-component supramolecular hydrogel, the mass ratio of tannic acid to steviol glycoside is 1.7:(1.01-2.41).

[0008] Furthermore, the tannic acid aqueous solution is obtained by uniformly mixing tannic acid and water and then subjecting the mixture to a heating treatment.

[0009] Furthermore, the mass volume ratio of the tannic acid to the water is (1.7-6.8) g:1 mL.

[0010] Furthermore, the heating treatment is carried out at a temperature of 70-90°C and for a time of 2-12 hours.

[0011] Furthermore, the stevioside aqueous solution is obtained by uniformly mixing stevioside and water and then subjecting the mixture to a heating treatment.

[0012] Furthermore, the mass volume ratio of the stevioside to the water is (2.41-4.02) g:1 mL.

[0013] Furthermore, the heating treatment is carried out at a temperature of 70-90°C and for a time of 1-8 hours.

[0014] The present invention also provides a two-component supramolecular hydrogel prepared according to the above preparation method.

[0015] The present invention also provides application of the above two-component supramolecular hydrogel in preparing bone adhesive.

[0016] The present invention also provides a bone adhesive, comprising the above-mentioned two-component supramolecular hydrogel.

[0017] The present invention discloses the following technical effects:

[0018] The invention adopts tannic acid and stevioside as raw materials, utilizes the benzene ring in the tannic acid molecule to generate π-π interaction, and obtains a self-assembled body; at the same time, the hydroxyl groups in the tannic acid molecule and the hydroxyl groups in the stevioside molecule generate hydrogen bond interaction to achieve chemical cross-linking, and finally prepares a two-component supramolecular hydrogel with a supramolecular cross-linked network structure.

[0019] In the two-component supramolecular hydrogel of the present invention, tannic acid and stevioside both contain rich hydroxyl groups, can form a close interaction with the bone surface, and can obtain a larger adhesive-bone interface bonding strength; tannic acid and stevioside are both natural small molecules of biological origin, and have good biocompatibility; tannic acid and stevioside have natural antibacterial ability, so the developed hydrogel bone adhesive has a good antibacterial effect, which is beneficial to avoid bacterial infection during bone repair. The bone adhesive is prepared using the hydrogel provided by the present invention, the preparation method is simple, and it can be repeatedly bonded during the use of bone bonding, which is beneficial to achieve more accurate bone bonding.

[0020] The bone adhesive prepared by using the two-component supramolecular hydrogel of the present invention can better meet the performance requirements of clinical bone adhesives, is a new type of bone adhesive with great application potential, and is more suitable for clinical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 The pictures are of the stevioside (St), tannic acid (TA) solution in Comparative Example 1-2 and the hydrogel (TA-St) prepared in Example 1-3; wherein A is stevioside; B is tannic acid; CE are the hydrogels prepared in Example 1-3 respectively;

[0023] Figure 2 TA-St hydrogels are scanning electron micrographs; wherein, AD are TA-St hydrogels prepared in Examples 1-4, respectively;

[0024] Figure 3 are the rheological test results of TA-St hydrogels; wherein AC are the TA-St hydrogels prepared in Examples 1-3, respectively;

[0025] Figure 4 X-ray diffraction patterns of TA-St hydrogel and pure TA and St powders prepared in Example 3;

[0026] Figure 5 NMR images of pure TA, St and TA / St mixture in deuterated water;

[0027] Figure 6 FTIR spectra of pure TA, St and freeze-dried samples of TA-St hydrogel prepared in Example 3;

[0028] Figure 7 The antibacterial effect of the TA-St hydrogel prepared in Example 3 on Escherichia coli and Staphylococcus aureus;

[0029] Figure 8 The results of the cytotoxicity test of the TA-St hydrogel prepared in Example 3 on rat bone marrow mesenchymal stem cells; A and C are the cell viability change diagrams when the rat bone marrow mesenchymal stem cells were co-cultured with the hydrogel for 24h and 48h, respectively; B and D are the laser confocal microscopy observation diagrams of the cells when the rat bone marrow mesenchymal stem cells were co-cultured with the hydrogel for 24h and 48h, respectively; the scale bars in B and D are both 50μm;

[0030] Fig. 9 Schematic diagram of the performance of the TA-St hydrogel bone adhesive prepared in Example 3 in repeatedly bonding broken bones;

[0031] Fig.10 Statistical graph of the bonding strength of the TA-St hydrogel bone adhesive prepared in Examples 1-3 to the bone interface. DETAILED DESCRIPTION

[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0033] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0037] Example 1

[0038] (1) Dissolve 1.70 g of tannic acid in 1 mL of water and heat at 80° C. for 2 h to obtain a tannic acid aqueous solution with a concentration of 1 mol / L;

[0039] (2) Dissolve 2.41 g of stevioside in 1 mL of water and heat at 80°C for 2 h to obtain a stevioside aqueous solution with a concentration of 3 mol / L;

[0040] (3) The tannic acid aqueous solution and the stevioside aqueous solution were mixed evenly and allowed to stand at room temperature for 12 h to form a tannic acid-stevioside based two-component supramolecular hydrogel TA 0.5 -St 1.5 .

[0041] Example 2

[0042] (1) Dissolve 3.40 g of tannic acid in 1 mL of water and heat at 80° C. for 6 h to obtain a tannic acid aqueous solution with a concentration of 2 mol / L;

[0043] (2) Dissolve 2.41 g of stevioside in 1 mL of water and heat at 80°C for 2 h to obtain a stevioside aqueous solution with a concentration of 3 mol / L;

[0044] (3) The tannic acid aqueous solution and the stevioside aqueous solution were mixed evenly and allowed to stand at room temperature for 12 h to form a tannic acid-stevioside based two-component supramolecular hydrogel TA 1.0 -St 1.5 .

[0045] Example 3

[0046] (1) Dissolve 3.40 g of tannic acid in 1 mL of water and heat at 80° C. for 6 h to obtain a tannic acid aqueous solution with a concentration of 2 mol / L;

[0047] (2) Dissolve 4.02 g of stevioside in 1 mL of water and heat at 80°C for 4 h to obtain a stevioside aqueous solution with a concentration of 5 mol / L;

[0048] (3) The tannic acid aqueous solution and the stevioside aqueous solution were mixed evenly and allowed to stand at room temperature for 24 h to form a tannic acid-stevioside based two-component supramolecular hydrogel TA 1.0 -St 2.5 .

[0049] Example 4

[0050] (1) Dissolve 6.80 g of tannic acid in 1 mL of water and heat at 80° C. for 12 h to obtain a tannic acid aqueous solution with a concentration of 4 mol / L;

[0051] (2) Dissolve 4.02 g of stevioside in 1 mL of water and heat at 80°C for 4 h to obtain a stevioside aqueous solution with a concentration of 5 mol / L;

[0052] (3) The tannic acid aqueous solution and the stevioside aqueous solution were mixed evenly and allowed to stand at room temperature for 48 hours to form a tannic acid-stevioside based two-component supramolecular hydrogel TA 2.0 -St 2.5 .

[0053] Example 5

[0054] (1) Dissolve 3.40 g of tannic acid in 1 mL of water and heat at 70°C for 12 h to obtain a tannic acid aqueous solution with a concentration of 2 mol / L;

[0055] (2) Dissolve 4.02 g of stevioside in 1 mL of water and heat at 70°C for 8 h to obtain a stevioside aqueous solution with a concentration of 5 mol / L;

[0056] (3) The tannic acid aqueous solution and the stevioside aqueous solution were mixed evenly and allowed to stand at room temperature for 24 h to form a tannic acid-stevioside based two-component supramolecular hydrogel TA 1.0 -St 2.5 .

[0057] Example 6

[0058] (1) Dissolve 3.40 g of tannic acid in 1 mL of water and heat at 90° C. for 2 h to obtain a tannic acid aqueous solution with a concentration of 2 mol / L;

[0059] (2) Dissolve 4.02 g of stevioside in 1 mL of water and heat at 90° C. for 1 h to obtain a stevioside aqueous solution with a concentration of 5 mol / L;

[0060] (3) The tannic acid aqueous solution and the stevioside aqueous solution were mixed evenly and allowed to stand at room temperature for 24 h to form a tannic acid-stevioside based two-component supramolecular hydrogel TA 1.0 -St 2.5 .

[0061] Comparative Example 1

[0062] 4.02 g of stevioside was dissolved in 2 mL of water and heated at 80° C. for 4 h to obtain a stevioside aqueous solution.

[0063] Comparative Example 2

[0064] Dissolve 6.80 g of tannic acid in 2 mL of water and heat at 80° C. for 12 h to obtain a tannic acid aqueous solution.

[0065] Test Case

[0066] The tannic acid-stevioside based two-component supramolecular hydrogel prepared in Examples 1-4 of the present invention and the tannic acid and stevioside solutions in Comparative Examples 1-2 were tested.

[0067] (1) Gelation performance test

[0068] Figure 1 The pictures are of the stevioside aqueous solution in Comparative Example 1, the tannic acid aqueous solution in Comparative Example 2, and the hydrogels prepared in Examples 1-3. Figure 1 It can be seen that under the same concentration conditions, tannic acid or stevioside cannot form hydrogel, but a two-component supramolecular hydrogel can be obtained by mixing tannic acid and stevioside, indicating that tannic acid and stevioside are both necessary raw materials for the preparation of this supramolecular hydrogel.

[0069] (2) Scanning electron microscope test

[0070] Figure 2 The following is a scanning electron micrograph of the hydrogel prepared in Example 1-4. Figure 2 It can be seen from the test results that all hydrogel samples have a dense microstructure without obvious porous structure, and with the increase of the mass content of tannic acid or stevioside in the hydrogel, the microstructure of the hydrogel becomes denser and smoother.

[0071] (3) Rheological properties test

[0072] Figure 3 The rheological test results of the hydrogels prepared in Examples 1-3 are shown in FIG. Figure 3 The test results show that the hydrogel samples all exhibit viscoelastic behavior, and with the increase of the mass content of tannic acid or stevioside in the hydrogel, the storage modulus (G′) and loss modulus (G″) both increase significantly, proving that more chemical cross-links are generated inside the hydrogel, which is consistent with the results of scanning electron microscopy observations.

[0073] (4) X-ray diffraction test

[0074] Figure 4 The X-ray diffraction patterns of the hydrogel prepared in Example 3 and pure tannic acid and stevioside are shown in FIG. Figure 4The test results show that tannic acid and stevioside themselves do not have the ability to form an ordered assembly structure, resulting in the formation of a hydrogel with a dense internal structure but still no ordered assembly, which is consistent with the results of scanning electron microscopy observations.

[0075] (5) Nuclear magnetic resonance hydrogen spectrum test

[0076] Figure 5 The following are the NMR images of pure tannic acid, steviol glycosides, and tannic acid / stevioside mixtures in deuterated water. Figure 5 It can be seen from the test results that after tannic acid and stevioside are mixed, the NMR peaks of tannic acid all move to the low field and the NMR peaks of stevioside move to the high field, indicating that there is an interaction between tannic acid and stevioside after mixing.

[0077] (6) Infrared spectrum test

[0078] Figure 6 The infrared spectra of pure tannic acid, stevioside and the freeze-dried sample of hydrogel prepared in Example 3 are shown in FIG. Figure 6 The test results show that compared with tannic acid or stevioside itself, the hydrogel samples are more attributable to intermolecular hydrogen bonds (3500-3300cm -1 ) showed a significant red shift, further proving the formation of hydrogen bonding between tannic acid and stevioside.

[0079] (7) Antibacterial test

[0080] Dilute the Escherichia coli or Staphylococcus aureus culture medium to 10 6 CFU / mL, and evenly drip 30μL of bacterial solution on the surface of the hydrogel sample prepared in Example 3. Use sterile tweezers to pick up the sterile covering film and cover it on the sample, making sure to flatten it so that the bacteria are evenly in contact with the sample, and the bacterial solution should not exceed the edge of the covering film. Place it in a 37°C constant temperature incubator and culture it for 18 hours. After the culture is completed, rinse the sample surface with 870μL of sterile saline, then extract the rinse liquid, make a continuous 10-fold dilution, and take 100μL of the dilution liquid and evenly apply it on the LB solid culture medium. Place it in a 37°C constant temperature incubator and culture it for 24 hours, take it out, take a picture and record the number of colonies.

[0081] Figure 7 The antibacterial effect of the hydrogel prepared in Example 3 on Escherichia coli and Staphylococcus aureus. Figure 7 It can be seen from the test results that the antibacterial rates of the hydrogel sample prepared in Example 3 of the present invention against Escherichia coli and Staphylococcus aureus are both above 99.9%, and the antibacterial property is very excellent.

[0082] (8) Cytotoxicity test

[0083] The cytotoxicity test by CCK-8 method was divided into two groups: control group and hydrogel group. The control group was added with 100 μL / well complete culture medium; the hydrogel group was added with 100 μL / well working solution with concentrations of 3.125 μM, 6.25 μM, and 12.5 μM, respectively. Three replicates were made for each treatment group. Rat bone marrow mesenchymal stem cells in the logarithmic growth phase were taken, and the cell count was performed and the cell concentration was adjusted to 5×10 3 / well were inoculated into 96-well plates and cultured overnight in a 5% CO2, 37°C constant temperature incubator. According to the above grouping treatment, cultured in a 5% CO2, 37°C constant temperature incubator for 24h and 48h. The culture medium was removed, each well was washed three times with PBS, and the culture medium containing 10% CCK-8 was added at 100μL / well. The cells were cultured in a 5% CO2, 37°C constant temperature incubator for 2h, and the absorbance value at 450nm was detected by an enzyme reader.

[0084] The cell live / dead staining experiment was divided into two groups: the control group and the hydrogel group. The control group was added with 1000 μL / dish of complete culture medium; the hydrogel group was added with 1000 μL / dish of 12.5 μM working solution. Rat bone marrow mesenchymal stem cells in the logarithmic growth phase were taken, and the cell count was performed and the cell concentration was adjusted to 1×10 5 / dish was inoculated into the confocal dish and cultured overnight in a 5% CO2, 37°C constant temperature incubator. According to the above grouping treatment, cultured in a 5% CO2, 37°C constant temperature incubator for 24h and 48h. Take 985.5μL PBS and mix with 10μL diluted reagent A (Calcein-AM) and 4.5μL reagent B (PI). Wash the cells in the confocal dish once with PBS to remove excess serum. Add staining solution at 1000μL / dish and incubate at room temperature in the dark for 15min. Use PBS to wash three times to terminate the staining, observe the results with a laser confocal microscope and take pictures to record.

[0085] Test results see Figure 8 .Depend on Figure 8 The test results show that the cell survival rate of the hydrogel sample of Example 3 of the present invention after co-culture with rat bone marrow mesenchymal stem cells for 24 hours was above 100% under three different concentration conditions, and the cell survival rate was still maintained above 95% after co-culture for 48 hours. Combined with the cell Live / dead staining experiment, it is further proved that the hydrogel has no obvious cytotoxicity.

[0086] (9) Bone adhesion performance test

[0087] The operation method of the bone fragment repeated bonding experiment is as follows: the hydrogel prepared in Example 3 is evenly spread on the cross section of the pig leg bone, and the pig leg bone is continuously pressed along the axis for 1 minute to obtain a bonded pig leg bone. If the cross section is not bonded neatly, the bonding can be repeated within 2 minutes until the ideal bonding effect is achieved.

[0088] Fig. 9 The hydrogel bone adhesive prepared in Example 3 is used to repeatedly bond broken bones. Fig. 9 It can be seen that the hydrogel prepared in Example 3 of the present invention can quickly and easily bond the pig bone section, and can be repeatedly bonded to adjust the bonding effect of the bone section before the adhesive exerts the maximum bonding effect. This property of the adhesive has great practical value and advantages in clinical use, and is conducive to obtaining the best bone bonding effect.

[0089] (10) Bone adhesion strength test

[0090] The bone bonding strength test method is as follows: the hydrogel bone adhesive prepared in Examples 1-3 is evenly spread on the bone section, pressed for 1 minute, and then left to stand for 10 minutes before testing using a universal testing machine. Fig.10 .

[0091] Depend on Fig.10 The test results show that the hydrogel prepared in Example 3 of the present invention has good adhesion to fresh bone sections, and the adhesion strength reaches 141.2 kPa. Compared with Examples 1 and 2, the adhesion strength of the hydrogel prepared in Example 3 is significantly improved, indicating that the mass content and mass ratio of tannic acid and steviol glycoside are closely related to the bone adhesion performance of the hydrogel adhesive.

[0092] In summary, it can be seen that the hydrogel bone adhesive of the present invention has excellent antibacterial properties, no obvious cytotoxicity, can be repeatedly bonded and has strong bone bonding strength, and is a bone adhesive product with great potential.

[0093] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a two-component supramolecular hydrogel, characterized in that: The method comprises the steps of uniformly mixing the tannic acid aqueous solution and the stevioside aqueous solution, and allowing the mixture to stand for cross-linking to obtain the two-component supramolecular hydrogel; In the two-component supramolecular hydrogel, the mass ratio of tannic acid to steviol glycoside is 1.7:(1.01-2.41).

2. The preparation method according to claim 1, characterized in that: The tannic acid aqueous solution is obtained by uniformly mixing tannic acid and water and then subjecting the mixture to a heating treatment.

3. The preparation method according to claim 2, characterized in that: The mass volume ratio of the tannic acid to the water is (1.7-6.8) g:1 mL.

4. The preparation method according to claim 2, characterized in that: The heating treatment is performed at a temperature of 70-90° C. and for a time of 2-12 hours.

5. The preparation method according to claim 1, characterized in that: The stevioside aqueous solution is obtained by uniformly mixing stevioside and water and then subjecting the mixture to a heating treatment.

6. The preparation method according to claim 5, characterized in that: The mass volume ratio of the stevioside to the water is (2.41-4.02) g:1 mL.

7. The preparation method according to claim 5, characterized in that: The temperature of the heating treatment is 70-90° C. and the time is 1-8 hours.

8. A two-component supramolecular hydrogel prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the two-component supramolecular hydrogel according to claim 8 in the preparation of bone adhesive.

10. A bone adhesive, characterized in that: The invention comprises the two-component supramolecular hydrogel as claimed in claim 8.